Slovak poetry in English translation after the collapse of state socialism: Tracing the trajectories of internationalisation - Hostová, Ivana (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2023)
Moving literary texts from a peripheral language to a hyper-central one (Heilbron 1999) goes against the general flow of translations, and agents involved in this process play crucial roles in it. In this article, on the case of English translations of Slovak poetry, I set out to investigate how such processes work. My research starts with assembling a bibliography of English translations of Slovak poetry published in book form between 1989 and 2020. The list contains no fewer than 2,500 poems by 161 poets, translated by more than 50 translators. A few observations from the quantitative analysis I conducted help answer such questions as what kind of agents translate poetry in these projects, who gets translated and how likely it is that the volumes reach an international readership. Subsequently, I use tools from Bourdieu’s field theory and Latour’s actor-network theory (ANT) to trace actor-networks pertaining to those translation projects concerning the rendering of two chosen Slovak poets who hold different positions in the Slovak literary field—Mila Haugová (born in 1942) and Milan Richter (born in 1948).